PENGARUH PROFITABILITAS, LEVERAGE DAN CORPORATE GOVERNANCE TERHADAP EFFECTIVE TAX RATE PERUSAHAAN LQ45 DI BURSA EFEK INDONESIA - Yenty, Yenty; Tipa, Handra (EDUTECH CONSULTANT, 2020)
The biggest obstacles in order to optimize taxes is tax avoidance or tax evasion. One of efforts to avoid the obtacles is by calculating the effective tax rate. The aim of this study is to verify several factors that can affect the effective tax rate in the company. The factors which are examined in this study are profitability, leverage, and corporate governance. This research is an empirical research with purposive sampling technique and requires secondary data which is annual reports of LQ45 companies that listing on the Indonesia Stock Exchange from 2014 to 2018. This study uses multiple regression analysis and version 24 of the SPSS program. The results of this study show taht debt to asset ratio, institutional ownership and audit committee affect the effective tax rate while return on assets does not affect the effective tax rate. However, the four variables above simultaneously affect the effective tax rate.